The Return of the Thucydides Trap: The Great Strategy of the United States and China in the Face of the Hegemonic Dispute from the Perspective of the Political Economy of World-Systems - Gerig, Malfred (Geopolítica(s). Revista de estudios sobre espacio y poder, 2021)
This article tries to carry out a critical analysis of the Grand Strategy of both the United States and China in the face of the reorientation of the centre of the global political economy to East Asia and the geopolitical rise of China. From a historical and global perspective, both the theoretical positions underlying the Grand Strategy of both powers and the empirical dynamics of the global political economy capable of modifying the course of geostrategic planning are analysed. To do this, first of all, a critique of the theoretical foundations with which the theories of international relations try to understand hegemonic disputes is made. Second, it analyses how the theoretical-political spectrum of the US Grand Strategy intends to face the challenge of China’s rise. Third, China’s foreign policy strategy is analysed to prevent its rise from generating a reaction in the power in relative decline. Finally, the three most widespread precepts in the literature on the hegemonic dispute are discussed.
Keywords: Great strategy; United States; China; global political economy; geopolitics